2011
DOI: 10.1017/s0950268810002906
|View full text |Cite
|
Sign up to set email alerts
|

Factors related toCampylobacterspp. carriage in client-owned dogs visiting veterinary clinics in a region of Ontario, Canada

Abstract: From July 2008 until May 2009, 240 client-owned pet dogs from seven veterinary clinics in the Region of Waterloo, Ontario, Canada participated in a study to determine pet-related management factors that may be associated with the presence of Campylobacter spp. in dogs. The prevalence of Campylobacter spp. carriage in our study population of pet dogs was 22%, with 19% of the dogs positive for C. upsaliensis, and 3% positive for C. jejuni. A significant risk factor from multivariable logistic regression models f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
41
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 36 publications
10
41
2
3
Order By: Relevance
“…hyointestinalis from a dog. Our work echoes the findings of previous studies, which have reported that C. jejuni and C. upsaliensis are the species most commonly documented in dogs and cats worldwide, while C. coli and C. lari have been rarely isolated (Baker et al, 1999;Sandberg et al, 2002;Hald et al, 2004;Koene et al, 2004;Wieland et al, 2005;Workman et al, 2005;Rossi et al, 2008;Acke et al, 2009aAcke et al, , 2009bParsons et al, 2010Parsons et al, , 2011Leonard et al, 2011;Carbonero et al, 2012). Conversely, C. helveticus has been frequently detected in cats (Shen et al, 2001;Wieland et al, 2005;Workman et al, 2005;Tsai et al, 2007;Rossi et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…hyointestinalis from a dog. Our work echoes the findings of previous studies, which have reported that C. jejuni and C. upsaliensis are the species most commonly documented in dogs and cats worldwide, while C. coli and C. lari have been rarely isolated (Baker et al, 1999;Sandberg et al, 2002;Hald et al, 2004;Koene et al, 2004;Wieland et al, 2005;Workman et al, 2005;Rossi et al, 2008;Acke et al, 2009aAcke et al, , 2009bParsons et al, 2010Parsons et al, , 2011Leonard et al, 2011;Carbonero et al, 2012). Conversely, C. helveticus has been frequently detected in cats (Shen et al, 2001;Wieland et al, 2005;Workman et al, 2005;Tsai et al, 2007;Rossi et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Host age was a risk factor in several previous studies, with young pets more likely to be colonised, mainly by C. upsaliensis (Wieland et al, 2005;Parsons et al, 2010;Leonard et al, 2011) and infrequently by C. jejuni (Hald et al, 2004). In the present study, C. jejuni was the predominant species and this could have hampered our ability to detect an association between age and Campylobacter carriage.…”
Section: Discussioncontrasting
confidence: 59%
“…These include the age of the animal, with puppies < 6 months and cats <36 months more frequently positive for Campylobacter spp. [21-23]; housing conditions, with dogs housed in kennels or shelters and outdoor cats with no access to litter trays, more at risk of campylobacter infections [23,24]; and dogs’ diet, with a higher risk of campylobacter infection for animals fed a homemade food diet [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Lefebvre et al 2006) and 5 surveys using real-time PCR (Inglis et al 2004;Chaban et al 2010;Himsworth et al 2010;PHAC 2010b;Van Dyke et al 2010). An additional 9 studies used PCR for confirmation or species identification (Lévesque et al 2006;Inglis et al 2007;Sutherland et al 2009;Jokinen et al 2010;Leonard et al 2011;Khan et al 2013aKhan et al , 2013bKhan et al , 2014Schmidt et al 2013). In these studies different primers targeting various gene regions were employed.…”
Section: Detection Methodsmentioning
confidence: 99%